Broadband Coherent Mid-Infrared Supercontinuum Generation in All-Chalcogenide Microstructured Fiber With All-Normal Dispersion - Xiao, Kun; Ye, Yudong; Min, Rui (Frontiers in Physics, 2022)
We demonstrated numerically the generation of broadband, coherent supercontinuum (SC) spectra in the mid-infrared region using dispersion-engineered all-chalcogenide microstructured fibers (MOFs). The 1-cm-long hexagonal fiber can be made with Ge11.5As24S64.5 glass as a low-refractive-index material embedded in a Ge11.5As24Se64.5 glass matrix. By optimizing the structural parameters, we determined a broad and flat all-normal-dispersion characteristic up to 14 μm. A highly coherent broadband SC with an intensity greater than −3 dB in the range from 5973 to 8695 nm is obtained when the fiber is pumped by a 7 μm laser with pulse duration of 50 fs and peak power of 6 kW. Flat-top SC of −30 dB level can be observed utilizing identical pump pulse parameters, covering wavelengths from 3823 to 13577 nm (>1.5 octaves). This broadband coherent MIR SC source can be applied in frequency metrology, optical coherence tomography, biomedical imaging, and few-cycle pulse compression.